Strategi Perencanaan dan Penanganan Drainase di Permukiman Kumuh Lingkungan Satria Kelurahan Penarukan, Buleleng - Kadek Tania Utami Putri; Putu Siskha Pradnyaningrum; Pande Putu Liani Darmayanti; Ni Nyoman Tiara Ayu Valentina (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
Penarukan Village in Buleleng Regency is confronted with issues of slum settlements, notably in the Satria neighborhood. The emergence of slum settlements in the Satria area is attributed to an inadequate drainage system. In response to this challenge, strategic planning and intervention are essential to optimize functionality in accordance with Minimum Service Standards (MSS). This aims to accommodate normal water flow, particularly during the rainy season, preventing waterlogging or flooding. The research is conducted to address the problem of inadequate drainage caused by blockages from waste, numerous holes in residents' yards, soil accumulation, clogging from kitchen and grass waste, and even structural damage. These factors contribute to the existence of slum settlements in the Satria community of Penarukan Village. The proposed intervention of strategy involves measures such as the installation of U-shaped ditches and infiltration wells, with a 5-meter gap between the first and second infiltration wells. The research methodology employs a descriptive-qualitative approach based on literature reviews and on-site observations. The qualitative method is used to collect, process, and analyze data obtained from literature reviews, interviews, and field observations. This study aims to provide valuable insights and practical solutions to enhance the drainage infrastructure, ultimately contributing to improved living conditions and the reduction of slum settlements in the Satria community of Penarukan Village.